Sehr gut. (Berlin : Stadt Berlin)
Ahearn, Charlie ; Ahearn, John ; B., Scott ; Bass, Beth B. Barbara ; Berei, Adele ; Blumenschein, Tabea ; Boetel, Hans ; Branca, Glen ; Feldmann, Hans-Peter ; Fetting, Rainer ; Fitzgibbon, Colen ; Hahn, Christine ; Hoffmeister ; Jud, Anne ; Kippenberger, Martin ; Kohlhöfer, Christof ; Krueger, Joachim ; Krueger, Klaus ; Lunch, Lydia ; Meuser ; Middendorf, Helmut ; Mitchell, Eric ; Otterness, Tom ; Utesch, Hella ; White, James ; Winter, Robin ; Zimmer, Bernd
44 p. : zw/w ill. ; 43 x 31 cm : groot formaat
Sehr gut, Stadt Berlin, [1979]
kunstcatalogus